Menilai tahap kepuasan pelajar Kejururawatan tahun akhir terhadap Aspek sokongan penyeliaan klinikal dl HUSM - Hussin, Nor Hazian Md (2007)
Introduction : Student's degree of satisfaction, in the context oft earning, is very important as a strategy and main dimension in order to improve the quality of nursing education. Student's satisfaction towards education's activities are not just helping the student to excel but supporting their professional development in the near future. Objectives: The aim of the study are to evaluate the degree of satisfaction among final year nursing students towards the aspect of clinical supervision at HUSM. The researcher wish to identify the support factors that influence students satisfaction and finally to examine the problems faced by students on the aspect of support. Methodology : A quantitative study design cross sectional study was used to explore a level of student's nursing final year satisfaction in clinical supervision. Sampling method are convenience and consensus sampling were used in this study. Focus group are nursing students on 4th year Degree Programme of Pusat Pengajian Sains Kesihatan (PPSK) and nursing students on 3rd year Diploma Programme of University Daml hnan (UDM) which had practical course at HUSM for more than one week. Results: The result showed that the score of the highest level satisfaction (69-115) for diploma nursing programme was 92.9% (f=26), meanwhile for the degree nursing programme was 86.1% (f=31 ). Score for the lowest level of satisfaction (23-68) for the diploma programme was 7.1% (f=2) and degree programme was 13.9% (f=5). Data analyzed by using independent t test (p=O.OOO) was showed that there are significant among personal, interpersonal and organization support with the level of satisfaction during clinical supervision. Tpe analysis finding for demography data by using chi-square (X.2) test showed that there is no significant difference (p>0.05) for all demography data with the level of satisfaction. Meanwhile in chi-square analysis (X.2), Pearson chisquare showed at the a, 0.05, p value =0.391. So that, there is no statistically significant diference between the level of satisfaction among degree and diploma programme. Conclusion : Majority of students was given positive feedback towards the supervision clinical. This shows that the supervision quality is at the better standard. There are significant between of personal, interpersonal and organization factors with level of satisfaction in clinical supervision. These factors also significant and consistent with the other study.